2012
DOI: 10.1021/la2037247
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Plutonium Oxide Nanoparticles

Abstract: Adsorption of monodisperse cubic plutonium oxide nanoparticles ("Pu-NP", [Pu(38)O(56)Cl(x)(H(2)O)(y)]((40-x)+), with a fluorite-related lattice, approximately 1 nm in edge size) to the muscovite (001) basal plane from aqueous solutions was observed in situ (in 100 mM NaCl background electrolyte at pH 2.6). Uptake capacity of the surface quantified by α-spectrometry was 0.92 μg Pu/cm(2), corresponding to 10.8 Pu per unit cell area (A(UC)). This amount is significantly larger than that of Pu(4+) needed for satis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 62 publications
6
43
2
Order By: Relevance
“…The second peak is broader and reaches up to 50 Å height from the surface. This distribution is similar to what has been observed upon adsorption (Schmidt et al, 2012b) and formation (Schmidt et al, 2013) of Pu nanoparticles on the muscovite-water interface, but the coverage of Th is smaller than those of Pu in the adsorbed nanoparticles (4.9 Th/A UC compared to 9.9 and 10.8 Pu/A UC , respectively).…”
Section: Structural Model Th-liclosupporting
confidence: 85%
See 2 more Smart Citations
“…The second peak is broader and reaches up to 50 Å height from the surface. This distribution is similar to what has been observed upon adsorption (Schmidt et al, 2012b) and formation (Schmidt et al, 2013) of Pu nanoparticles on the muscovite-water interface, but the coverage of Th is smaller than those of Pu in the adsorbed nanoparticles (4.9 Th/A UC compared to 9.9 and 10.8 Pu/A UC , respectively).…”
Section: Structural Model Th-liclosupporting
confidence: 85%
“…Uptake quantification performed ex situ after two flushing steps finds a significantly smaller coverage of h a = 1.6 ± 0.3 Th/A UC than the coverage h RAXR = 4.9 Th/A UC found by RAXR. The plutonium nanoparticles reported previously were not desorbed by similar flushing steps, and RAXR and alpha spectrometry found matching coverages in these experiments (Schmidt et al, 2012b(Schmidt et al, , 2013. For Th extended outer sphere complexes, however, it has been demonstrated that the sorption reaction is partly reversible (Schmidt et al, 2012a).…”
Section: Cation Effectsupporting
confidence: 77%
See 1 more Smart Citation
“…The measured Pu coverage was also larger than the value expected for the surface charge compensation by trivalent Pu, and was interpreted to be indicative of an in situ oxidation of plutonium followed by formation of Pu clusters on the surface. In a second study, the sorption of Pu-oxo-nanoparticles at the muscovite (0 0 1) basal plane has been elucidated (Schmidt et al, 2012) revealing specifics of the nanoparticle-mineralsurface interaction. The nanoparticles were shown to adsorb on the (0 0 1) basal plane in one well-defined layer as well as in randomly distributed aggregates from an aqueous solution of monodisperse plutonium-oxide nanoparticles ([Pu 38 O 56 Cl x (H 2 O) y ] (40Àx)+ , [Pu] tot = 10 À3 mol/L, pH = 2.6).…”
Section: X-ray Reflectivitymentioning
confidence: 99%
“…An understanding of Th chemistry for its own sake is useful to help delineate the similarities and differences in the behavior of these two elements. Toward this end, and to complement our efforts relevant to the understanding Pu migration in the environment (Soderholm et al, 2008;Fenter et al, 2010;Wilson et al, 2010;Schmidt et al, 2012), we report on experiments probing Th adsorption onto the (0 0 1) surface of muscovite mica.…”
Section: Introductionmentioning
confidence: 99%